Nobody Puts Filmmaking in a Corner! - Wood, Martin (Organizational Aesthetics, 2015)
Questions of how we effectively share new insights with a wider public have entered upon the debate about all research activity in organisation studies. How can scholars demonstrate impact on audiences, users, and the beneficiaries of research in this field of work?